Analisis Kebutuhan Media Pembelajaran Word Search Puzzle pada Materi AlKhabir Kelas VII MTs Hidayatul Muhajirin Palangkaraya - Safitri, Suci Aulia; Maulana, Ahmad (MASALIQ, 2024)
This research is to analyze the need for using Word Search Puzzle learning media in Al-Khabir material in class VII MTs Hidayatul Muhajirin Palangka Raya. The research uses a mixed method, combining quantitative and qualitative approaches, with data collected through questionnaires and interviews. The research results show that 79% of students have high interest in using Word Search Puzzle, while 21% are less interested. This media is effective in increasing students' motivation, involvement and understanding of the material being taught. Apart from that, Word Search Puzzle also stimulates critical thinking skills, accuracy and concentration. And as many as 59% of teachers only use media in the form of modules such as textbooks or worksheets, while the other 41% do not use technology-based media in learning. Thus, this research recommends the development of innovative learning media to increase student involvement in the teaching and learning process in accordance with educational needs in the digital era.